Main group metal lone-pair⋯π(arene) interactions: a new bonding mode for supramolecular associations - Caracelli, Ignez; Zukerman-Schpector, Julio; Haiduc, Ionel; Tiekink, Edward R. T. * (Royal Society of Chemistry, 2016)
Crystal structures of the heavier main group elements in low oxidation states have been evaluated for the presence of supramolecular elementĲlp)⋯π(arene) interactions that are structure-directing. It is revealed that when present, these interactions lead to zero-dimensional, binuclear aggregates but higher-nuclearity species are sometimes observed, with one-dimensional supramolecular chains of varying topology being prominent. By contrast, two-dimensional aggregation based on elementĲlp)⋯π(arene) interactions are rare. In summary, interactions of main group metal lone-pairs with aromatic rings are revealed as synthons capable of assembling molecules into supramolecular aggregates.